2015
DOI: 10.3171/2014.10.spine14233
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in acute fractures of the cervical spine: the role of opportunistic CT screening

Abstract: OBJECT Recently published data make it possible to generate estimates of bone mineral density (BMD) by using CT attenuation; this innovation can save time and reduce costs. Although advanced age is associated with reduced BMD, especially in patients with a fracture of C-2, relatively few patients ever undergo formal dual x-ray absorptiometry studies. To the authors' knowledge, this is the first study to assess the utility of this technique in elucidating BMD in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…This hypothesis is supported further as qualitatively assessed bone mineral density (BMD) was reported to be lower in patients with TOFs than in those without . Additionally, a recent study has suggested that the prevalence of osteoporosis and osteopenia in odontoid fracture patients is relatively high …”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…This hypothesis is supported further as qualitatively assessed bone mineral density (BMD) was reported to be lower in patients with TOFs than in those without . Additionally, a recent study has suggested that the prevalence of osteoporosis and osteopenia in odontoid fracture patients is relatively high …”
Section: Introductionmentioning
confidence: 77%
“…Several studies have shown that low bone quality is associated with an increased risk for odontoid fractures . Until now, a quantitatively and phantom‐calibrated measurement method assessing bone quality in TOFs and respective controls were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in BMD values measured by DEXA and QCT are widely recognized (20262728). The reason is possibly related to different bone turnover between the cancellous and the cortical bone.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies examined standard surgical intervention before radiotherapy, whereas one recent study evaluated laser interstitial thermotherapy (LITT). 39 Three studies had long-term follow-up, except the LITT study that reported perioperative outcomes with a short median follow-up time of 4.7 months. The mean local failure rate was 17.1% with a mean time to local recurrence of 13.6 months.…”
Section: Resultsmentioning
confidence: 99%
“…Complications were minimal in all four studies and included hardware failure in a selected group of patients, only some of which required reoperation. 37,3941 Of note, some patients developed toxicity because of SRS, which included GI, GU, and musculoskeletal manifestations. 40 …”
Section: Resultsmentioning
confidence: 99%